2019
DOI: 10.1534/genetics.119.302004
|View full text |Cite
|
Sign up to set email alerts
|

Filamentation Regulatory Pathways Control Adhesion-Dependent Surface Responses in Yeast

Abstract: Signaling pathways can regulate biological responses by the transcriptional regulation of target genes. In yeast, multiple signaling pathways control filamentous growth, a morphogenetic response that occurs in many species including fungal pathogens. Here, we examine the role of signaling pathways that control filamentous growth in regulating adhesion-dependent surface responses, including mat formation and colony patterning. Expression profiling and mutant phenotype analysis showed that the major pathways tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 177 publications
(232 reference statements)
1
33
0
Order By: Relevance
“…This suggests Nfg1p, Rgd2p, Rpi1p, and Tip1p might not turn off invasive growth like Dig1p, but instead modulate it in a specific context. One way the fMAPK pathway regulates invasive growth is by regulating the expression of FLO11, which encodes the cells' major adhesion molecule (LO AND DRANGINIS 1996;MADHANI et al 1999;RUPP et al 1999;ROBERTS et al 2000;HALME et al 2004;BORNEMAN et al 2006;VEELDERS et al 2010;ADHIKARI AND CULLEN 2014;KRAUSHAAR et al 2015;BARUA et al 2016;REYNOLDS 2018;CHOW et al 2019b;BRUCKNER et al 2020). RT-qPCR analysis showed that the expression of FLO11 was elevated in the nfg1∆, rgd2∆, and tip1∆ mutants compared to wild type, indicating these genes have an inhibitory effect on FLO11 expression (Fig.…”
Section: The Fmapk Pathway Induces Target Genes That Negatively Regulates Invasive Growthmentioning
confidence: 97%
See 3 more Smart Citations
“…This suggests Nfg1p, Rgd2p, Rpi1p, and Tip1p might not turn off invasive growth like Dig1p, but instead modulate it in a specific context. One way the fMAPK pathway regulates invasive growth is by regulating the expression of FLO11, which encodes the cells' major adhesion molecule (LO AND DRANGINIS 1996;MADHANI et al 1999;RUPP et al 1999;ROBERTS et al 2000;HALME et al 2004;BORNEMAN et al 2006;VEELDERS et al 2010;ADHIKARI AND CULLEN 2014;KRAUSHAAR et al 2015;BARUA et al 2016;REYNOLDS 2018;CHOW et al 2019b;BRUCKNER et al 2020). RT-qPCR analysis showed that the expression of FLO11 was elevated in the nfg1∆, rgd2∆, and tip1∆ mutants compared to wild type, indicating these genes have an inhibitory effect on FLO11 expression (Fig.…”
Section: The Fmapk Pathway Induces Target Genes That Negatively Regulates Invasive Growthmentioning
confidence: 97%
“…Transcriptional targets of the fMAPK pathway have been identified by comparative expression profiling (MADHANI et al 1999;ROBERTS et al 2000;HEISE et al 2010; ADHIKARI AND CULLEN 2014; VAN DER FELDEN et al 2014;CHOW et al 2019b). In Adhikari et al 2014, wild- (CULLEN et al 2004;VADAIE et al 2008;PITONIAK et al 2009)], KSS1 [MAP kinase, (COURCHESNE et al 1989;ROBERTS AND FINK 1994;BARDWELL et al 1998a)], STE12 and TEC1 LALOUX et al 1990;CHOU et al 2006), are induced by the fMAPK pathway to generate positive feedback (Fig.…”
Section: Characterizing Transcriptional Targets Of the Fmapk Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Relative gene expression was calculated using the 2 − Δ Ct formula, where Ct is defined as the cycle at which fluorescence was determined to be statistically significant above background; ΔCt is the difference in Ct of the gene of interest and the housekeeping gene ( ACT1). The primers used were: MSB2 forward (5′-CACTGCAAGCAGGTGGCTCT-3′), MSB2 reverse (5′-GAGGAGCCCGACAGTGTTGC-3′); HKR1 forward (5′-AAACCATGGGCGAAAATGGC-3′), HKR1 Reverse (5′-AAGGCAGGGGCTGTGAATAC-3′); KSS1 forward (5′-CCCAAGTGATGAGCCGGAAT-3′), KSS1 reverse (5′-TGGGCACTTCTTCCTCCTCT-3′); SHO1 forward (5′-AACTACGATGGGAGACACTTTG-3′), SHO1 reverse (5′-TCGTAAGCATCATCGTCATCAG-3′) (A dhikari and C ullen 2014); TEC1 forward (5′-ATGTTTCCAGAAGCCGTAGTT-3′), TEC1 reverse (5′-TTTAGCACCCAGTCCAGTATTT-3′) (A dhikari and C ullen 2014); STE12 forward (5′-GCAATCTTACCCAAACGGAATG-3′), STE12 reverse (5′-AATCGTCCGCGCCATAAA-3′) (A dhikari and C ullen 2014); FLO11 forward (5′-CACTTTTGAAGTTTATGCCACACAAG-3′), FLO11 reverse (5′-CTTGCATATTGAGCGGCACTAC-3′) (C hen and F ink 2006) and ACT1 forward (5′-TGGATTCCGGTGATGGTGTT-3′), ACT1 reverse (5′-CGGCCAAATCGATTCTCAA-3′) (C how et al 2019b). Experiments were performed with two independent biological replicates and two technical replicates for each biological replicate.…”
Section: Methodsmentioning
confidence: 99%